Analisis Amaliyah Ibadah Nahdlatul Ulama dan Muhammadiyah dalam Membangun Ukhuwah Islamiyyah - Nofitayanti, Nofitayanti; Supriadi, Udin (PT. Student Rihlah Indonesia, 2025)
The purpose of this research is to analyze the worship practices of Nahdlatul Ulama and Muhammadiyah in building ukhuwah Islamiyyah. This research uses a qualitative approach and literature study method. Based on the results of the discussion, the base of the differences between NU and Muhammadiyah lies in their differences in understanding the basic principles of the methodology of determining the law (istinbath). This initial difference is born due to differences in perspective, which then has consequences for differences in how to determine the law and then the legal product itself. The last mentioned difference will lead to differences in daily religious rituals (amaliyah yaumiyyah). Things like this at least lead us to the understanding that it is unlikely that humans around the world will be in one type of thinking. Allah SWT has given them different inclinations, different intellectual capacities, and different destinies. So differences, especially in matters of khilafiyyah far'iyyah are a necessity that must be addressed wisely. Rasulullah SAW has also confirmed the difference; ikhtilafu ummati rahmah.